Young Children's Play Practices with Digital Tablets Playful Literacy - Fróes, Isabel (Emerald Publishing, 2019)
This book focuses on how young children play and have fun while indulging in digital worlds, discovering and problem-solving with a variety of narratives and interfaces encountered on these digital playgrounds. These playful encounters are richer experiences than one might expect. Through engaging with digital interfaces, children expand their visual and verbal vocabulary, plus develop an embodied vocabulary that emerges out of the interactions. The book presents two sets of approaches in how to collect data with young children, and it proposes five key aspects, vocabulary, design, play, interaction and attachment, which cover the base of children's play with current digital technologies.